Assessing intergenerational access to resources: using criteria and indicators in West Kalimantan, Indonesia - Colfer, C.J.P.; Wadley, R.L.; Harwell, E.; Prabhu, Ravi (Resources for the Future and Center for International Forestry Research, 2001)
This chapter makes use of data from research conducted in 1996 in and around Danau Sentarum Wildlife Reserve in West Kalimantan, Indonesia. Its initial purpose was to contribute to the development of principles, criteria and indicators for sustainable forest management. The particular topic investigated here is “intergenerational access to resources“ in sustainable forest management. Three methods are briefly described, along with illustrative cases and evidence demonstrating aspects of SIAR that contribute to sustainable forest management. A scoring system, linked to the CIFOR Generic C&I (criteria and indicators), is also presented. Evidence of this kind can contribute to our understanding of the causal links between intergenerational access to resources and sustainable forest management.